Investigative study on IOT technology acceptance by elderly using Technology Acceptance Model (TAM) - Komalaa, Balan (2024)
The rapid expansion of Internet of Things (IoT) technology has significantly impacted various aspects of our daily lives, including healthcare, communication, and home automation. However, little attention has been given to understanding how older individuals perceive and interact with this technology. This study aims to fill this gap by investigating the acceptance of older adults towards IoT technology, utilizing the well-established Technology Acceptance Model (TAM). During the research, I examined the usage patterns of older adults concerning IoT technology. I focused on key aspects such as ease of use, perceived usefulness, and other factors that influence their adoption and satisfaction with it. To gather data for my study, I engaged in conversations and interviews with a diverse group of older individuals from various socio-economic backgrounds. My findings underscore critical factors that shape the willingness of older adults to embrace IoT technology. These insights offer valuable guidance for devising strategies to enhance the elderly population’s engagement with IoT devices, potentially leading to improvements in their quality of life, healthcare management, and social connections. This investigative study contributes to my existing knowledge by focusing on the unique challenges and opportunities associated with IoT technology acceptance among older adults. Furthermore, it confirms the TAM model’s effectiveness in understanding how distinct demographic groups interact with technology. My research findings can serve as valuable inputs for policymakers, technology developers, and healthcare providers, helping them design and implement IoT solutions that cater to the specific needs and preferences of older individuals.